2019
DOI: 10.1016/j.ijmecsci.2017.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Frequency domain homogenization for the viscoelastic properties of spatially correlated quasi-periodic lattices

Abstract: Frequency domain homogenization for the viscoelastic properties of spatially correlated quasi-periodic lattices,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 80 publications
(64 reference statements)
1
27
0
Order By: Relevance
“…Therefore, the main contributing of this work lies in development of the analytical formulae for shear modulus of monoplanar and multiplanar hexagonal nanostructures and nano-heterostructures. In this context, it can be noted that the mechanics of honeycomb-like structural form is investigated extensively in micro and macro scales based on principles of structural mechanics [49][50][51][52][53][54][55].…”
Section: Shear Modulus Of Hexagonal Nanostructures and Heterostructuresmentioning
confidence: 99%
“…Therefore, the main contributing of this work lies in development of the analytical formulae for shear modulus of monoplanar and multiplanar hexagonal nanostructures and nano-heterostructures. In this context, it can be noted that the mechanics of honeycomb-like structural form is investigated extensively in micro and macro scales based on principles of structural mechanics [49][50][51][52][53][54][55].…”
Section: Shear Modulus Of Hexagonal Nanostructures and Heterostructuresmentioning
confidence: 99%
“…Wang et al [22] proposed the re-entrant star-shaped honeycomb, and studied the deformation modes under different impact velocities, and found that the structure exhibits excellent impact resistance with the same cell wall thickness compared with classical re-entrant honeycomb and star-shaped honeycomb. Mukhopadhyay et al [23,24] developed an analytical framework to predict the equivalent in-plane elastic moduli of irregular auxetic honeycombs and the effect of viscoelasticity on irregular hexagonal lattices.…”
Section: Introductionmentioning
confidence: 99%
“…In case of mono‐planar structural configurations the atoms are placed in a single plane to form the lattice‐like forms (such as graphene and hBN), while the atoms are placed in multiple planes in multi‐planar 2D materials (such as stanene and MoS 2 ). The unit cell [ 49–52 ] of a 2D material lattice could either be formed using multiple atoms (such as hBN and MoS 2 ) or one single atom (such as graphene and stanene), based on which the 2D materials could further be classified to have heterogeneous and homogeneous atomic distribution, respectively. Depending on the mono or multi‐planar configuration and homogeneity or heterogeneity in the atomic distribution, the nanostructures of 2D materials can be classified into four different groups as shown in Figure 1A–D.…”
Section: Resultsmentioning
confidence: 99%